2015
DOI: 10.1155/2015/814043
|View full text |Cite
|
Sign up to set email alerts
|

Synoptic-Scale Precursors to Tropical Cyclone Rapid Intensification in the Atlantic Basin

Abstract: Forecasting rapid intensification (hereafter referred to as RI) of tropical cyclones in the Atlantic Basin is still a challenge due to a limited understanding of the meteorological processes that are necessary for predicting RI. To address this challenge, this study considered large-scale processes as RI indicators within tropical cyclone environments. The large-scale processes were identified by formulating composite map types of RI and non-RI storms using NASA MERRA data from 1979 to 2009. The composite fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
(47 reference statements)
1
11
0
Order By: Relevance
“…This relationship between increase in outflow magnitude and increase in TC intensity is in good agreement with many studies that previously identified such a relationship [e.g., Sadler, 1976;Chen and Gray, 1986;Merrill, 1988;Molinari and Vollaro, 1989;Pfeffer and Challa, 1992;Wu and Emanuel, 1994;Frank and Ritchie, 1999;Hanley et al, 2001;Kimball and Evans, 2002;Rappin et al, 2011]. The inward radial progression during intensification noted in both TCs is a result that has not received as much attention, but that agrees with the enhanced divergence (and subsequent mass evacuation from the core) arguments of Molinari et al [1995] and Grimes and Mercer [2015]. Indeed, as was found by Emanuel [2012] and Wang et al [2014], greater outflow provides a critical connection between the TC boundary layer and the upper troposphere environment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This relationship between increase in outflow magnitude and increase in TC intensity is in good agreement with many studies that previously identified such a relationship [e.g., Sadler, 1976;Chen and Gray, 1986;Merrill, 1988;Molinari and Vollaro, 1989;Pfeffer and Challa, 1992;Wu and Emanuel, 1994;Frank and Ritchie, 1999;Hanley et al, 2001;Kimball and Evans, 2002;Rappin et al, 2011]. The inward radial progression during intensification noted in both TCs is a result that has not received as much attention, but that agrees with the enhanced divergence (and subsequent mass evacuation from the core) arguments of Molinari et al [1995] and Grimes and Mercer [2015]. Indeed, as was found by Emanuel [2012] and Wang et al [2014], greater outflow provides a critical connection between the TC boundary layer and the upper troposphere environment.…”
Section: Discussionsupporting
confidence: 91%
“…The inward radial progression during intensification noted in both TCs is a result that has not received as much attention, but that agrees with the enhanced divergence (and subsequent mass evacuation from the core) arguments of Molinari et al . [] and Grimes and Mercer []. Indeed, as was found by Emanuel [] and Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…As the primary goal of this research was the identification of variables and spatial locations most favorable for distinguishing RI and non-RI storms, discriminatory statistical methods were needed. One method, rotated principal component analysis (RPCA), has been shown to be useful in discriminating meteorological environments of different types [11][12][13][14]. These studies also used permutation testing to evaluate magnitude differences in diagnostic variables for each environment.…”
Section: Rpcamentioning
confidence: 99%
“…While S-mode helped reveal the difficulties in identifying relevant RI/non-RI distinguishing characteristics, the results did not provide the necessary discrimination capability of interest in this work. Recent work has shown the value of composite analysis with T-mode RPCA in identifying discriminating characteristics for different meteorological event types [11,12]. Following the methodology of [11,12], a T-mode varimax-rotated RPCA [11,16], conducted simultaneously on all GEFS reforecast fields, was completed on all RI events and all non-RI events separately.…”
Section: T-mode Rpcamentioning
confidence: 99%
See 1 more Smart Citation